Portal Sul da Chapada Diamantina: diagnóstico e os caminhos para o desenvolvimento - SOUTO, Roberto Lucas Spínola (2017)
This dissertation aims to understand what the real needs for the development of the region South Portal of the Chapada Diamantina are being contemplated by the policies implemented by the public power. The case study is carried out through the understanding of the real needs of the region from the documental research of secondary data, semi-structured interviews with government and society representatives and field research, with research "in loco" by the author, for later analysis of which of these needs are being contemplated in the actions of the public power. The work begins with a bibliographical review approaching the region’s concept, essential for the spatial clipping and definition of the polygon to be studied; The relation of hierarchy that is established between the cities and the organization in urban networks, aiming at understanding the arrangement formed by the municipalities; and report the instruments of municipal planning and the proposal of regionalization of the State of Bahia, as a demonstration of the different scales of public power in promoting development. Brief considerations on regional development theories are made - looking at classics such as Perroux, Myrdal, Hirschman, Rostow, Rosenstien-Rodan, Nurkse and North - and to the more recent discussions on endogenous and local development, since they represent "models" of the path that must be taken to achieve development. After the delimitation of the region South Portal of the Chapada Diamantina, a socioeconomic analysis is presented and the State's performance is evaluated in the face of the needs for the economic and social development of the region. It was verified that the performance of the public power doesn't contemplate the real needs of the region. This fact is related to the low investment capacity of municipalities and lack of political unity that makes it difficult to obtain resources from other federal entities. Currently, income in the region is dependent on public power. The agricultural sector that represented the region's main source of income declined due to a lack of adequate water infrastructure, potentializing the consequences of drought. Tourism is little explored and there is no prospect in the short term regarding mineral exploration in the region, due to the inefficiency of the logistics infrastructure. Advances in the health sector, especially in the private sector, present good prospects for investments to remain. The difficulty in guaranteeing adequate conditions to the vicinal roads and the lack of electric power in a considerable number of properties represent a hindrance to the familiar agriculture, important element in the distribution of the income. The lack of an entrepreneurial class is highlighted, since even in the face of the comparative advantages of the region, little is done, increasing the degree of dependence on governmental actions. The low degree of coverage of the sewage and water distribution network may be linked to greater vulnerability to diseases for those residing in areas not covered by the services and the need to seek technical or higher education in other regions helps in the perpetuation of "privilege" of higher income families